Meningkatkan Kesadaran Remaja terhadap Permasalahan yang dihadapi Melalui Psikoedukasi - Nurmaulia Khotmi; Elisa Sulistia Fitri; Baiq Zulvita Rahayu; Fathul Azmi (Lembaga Pengembangan Kinerja Dosen, 2024)
Adolescents are individuals who are in the process of developing into a more mature or adult. During this time, individuals often experience problems that originate from themselves or from outside the individual. The purpose of this psychoeducation is so that adolescents are able to recognize and understand the conditions caused by the problems that arise in these adolescents. By recognizing and understanding the problems, it is hoped that the adolescents will be able to help themselves to overcome their problems so that these adolescents can become productive and happy adolescents. This psychoeducational activity is carried out with face-to-face seminars. The method used in this activity is action research or often called Action Research. The process of this method is that it starts from identifying the problem, developing a service activity plan, implementing service activities and finally evaluating the objectives of the service carried out. The implementation of activities in the form of material presentation on